1994
DOI: 10.1007/bf00710418
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and therapy for a patient with vitamin B12‐responsive methylmalonic acidaemia

Abstract: The prenatal therapy is described of a patient with vitamin B12-responsive methylmalonic acidaemia during the last 10 days of gestation with oral administration of vitamin B12 (20 mg/day) given to a mother did not normalize her urinary excretion of methylmalonic acid (MMA), which was 14.5 mmol/mol creatinine at 32 weeks of gestation. Before delivery, the mother was excreting 18.9 +/- 3.3 mmol MMA/mol creatinine (mean value at 7 days after vitamin B12 therapy), as well as at 32-37 weeks of gestation with no the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…MMA is a treatable and preventable genetic metabolic disorder. Studies have shown that prenatal high‐dose VB12 intrauterine therapy can enhance the prognosis of MMA patients 30 . In addition, postpartum low‐protein diets, mecobalamin, or L‐carnitine can effectively prevent or mitigate neurological damage 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMA is a treatable and preventable genetic metabolic disorder. Studies have shown that prenatal high‐dose VB12 intrauterine therapy can enhance the prognosis of MMA patients 30 . In addition, postpartum low‐protein diets, mecobalamin, or L‐carnitine can effectively prevent or mitigate neurological damage 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that prenatal high-dose VB12 intrauterine therapy can enhance the prognosis of MMA patients. 30 In addition, postpartum low-protein diets, mecobalamin, or L-carnitine can effectively prevent or mitigate neurological damage. 31 Hence, early diagnosis and intervention are vital for MMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports of maternal treatment with oral or intramuscular vitamin B12 for prenatal treatment of fetal methylmalonic acidemia (MMA) date as far back as 1975 (Ampola et al ., 1975; van der Meer et al ., 1990; Soda et al ., 1995; Zass et al ., 1995; Spada et al ., 1999; Huemer et al ., 2005; Zhang et al ., 2008). MMA can present prenatally as growth restriction or dilated cardiomyopathy (De Bie et al ., 2009), or postnatally with recurrent vomiting, failure to thrive, developmental retardation, and hepatomegaly.…”
Section: Therapy For Fetal Inborn Errors Of Metabolismmentioning
confidence: 99%
“…However, prenatal treatment is not always accompanied by improvements in biochemical markers of disease severity or the prevention of postnatal complications. This highlights the lack of knowledge regarding optimum dosing (Soda et al ., 1995) and the influence of fetal treatment on long-term outcomes (Huemer et al ., 2005). Monitoring the efficacy of prenatal treatment by measurement of odd-numbered fatty acid accumulation in newborn adipose tissue has been attempted, but its correlation with the prevention of neuropathology is unknown (Zass et al ., 1995).…”
Section: Therapy For Fetal Inborn Errors Of Metabolismmentioning
confidence: 99%